Assessment on the Impact on Human Health, Environment, Water and Soil by Disposing Household Expired Drugs: A Cross-Sectional Study in China - Mahara G; Wu Z; Ge Q; Li Z; Zhang J (Dove Medical Press, 2021)
Gehendra Mahara,1,* Zhihong Wu,2,* Qi Ge,1 Zhiwei Li,1 Jinxin Zhang1 1Department of Medical Statistics and Epidemiology, School of Public Health, Sun Yat-Sen University, Guangzhou, 510080, People’s Republic of China; 2Research Center, Baiyunshan Hejigong Pharmaceutical Factory, Guangzhou Baiyunshan Pharmaceutical Holdings Co., Ltd, Guangzhou, 510080, People’s Republic of China*These authors contributed equally to this workCorrespondence: Jinxin ZhangSchool of Public Health, Sun Yat-Sen University, Guangzhou, 510080, People’s Republic of ChinaTel +86-20-87332453Email zhjinx@mail.sysu.edu.cnBackground: The household expired drugs disposal has been a huge public issue in many countries, including China, which may affect various side and toxic effects on human health and environment, water resources, and soil too. This paper explores the knowledge, attitude, and practice of Guangzhou city residents regarding household expired drugs and their effect on human health and provided the scientific pieces of evidence to carry out the long-term recovery mechanism for expired medicines.Methods: An observational, cross-sectional study was conducted using a self-structured questionnaire. Descriptive analysis, including univariate and unconditional logistic regression models, was carried out to analyze the data.Results: A total of 613 community residents with a 99.4% response rate enrolled for the study. More than half 60.2% of residents stated that expired drugs pollute the environment, soil, and water resources, where 81.2% of respondents knew that it would produce side effects or toxic effects. However, still, 71.6% of respondents disposed of directly into the trash bin or sink, and, only 24.8% had good practice that they use a designed recycling bin. Likewise, only 8.3% of respondents placed expired drugs into collection points nearly 3– 5 times in a year, while 65.1% of participants never disposed of in the collection point, which found a worse practice.Conclusion: Overall, the knowledge, attitude, and practice of Guangzhou residents regarding household expired drugs disposal were not ideal. To improve the resident’s awareness about family expired drugs disposal, ensure the financial support for the recycling process, establish an accessible and acceptable recycling point, and introduce relevant laws and regulations for the long-term mechanism.Keywords: household, expired drugs, knowledge, attitude, practice, collection point, Guangzhou, China